Quantifying the Primary Emissions and Photochemical Formation of Isocyanic Acid Downwind of Oil Sands Operations - Liggio, John; Stroud, Craig A.; Wentzell, Jeremy J. B.; Zhang, Junhua; Sommers, Jacob; Darlington, Andrea; Liu, Peter S. K.; Moussa, Samar G.; Leithead, Amy; Hayden, Katherine; Mittermeier, Richard L.; Staebler, Ralf; et al. (ENVIRONMENTAL SCIENCE & TECHNOLOGY, 2017)
Isocyanic acid (HNCO) is a known toxic species and yet the relative importance of primary and secondary sources to regional HNCO and population exposure remains unclear. Off-road diesel fuel combustion has previously been suggested to be an important regional source of HNCO, which implies that major industrial facilities such as the oil sands (OS), which consume large quantities of diesel fuel, can be sources of HNCO. The OS emissions of nontraditional toxic species such as HNCO have not been assessed. Here, airborne measurements of HNCO were used to estimate primary and secondary HNCO for the oil sands. Approximately 6.2 +/- 1.1 kg hr(-1) was emitted from off-road diesel activities within oil sands facilities, and an additional 116-186 kg hr(-1) formed from the photochemical oxidation of diesel exhaust. Together, the primary and secondary HNCO from OS operations represent a significant anthropogenic HNCO source in Canada. The secondary HNCO downwind of the OS was enhanced by up to a factor of 20 relative to its primary emission, an enhancement factor significantly greater than previously estimated from laboratory studies. Incorporating HNCO emissions and formation into a regional model demonstrated that the HNCO levels in Fort McMurray (similar to 10-70 km downwind of the OS) are controlled by OS emissions; > 50% of the monthly mean HNCO arose from the OS. While the mean HNCO levels in Fort McMurray are predicted to be below the 1000 pptv level associated with potential negative health impacts, (similar to 25 pptv in August-September), an order of magnitude increase in concentration is predicted (250600 pptv) when the town is directly impacted by OS plumes. The results here highlight the importance of obtaining at-source HNCO emission factors and advancing the understanding of secondary HNCO formation mechanisms, to assess and improve HNCO population exposure predictions.